A decolonial political geography of resistance and digital infrastructural harm in Cameroon and Ethiopia - Murrey, A (Taylor & Francis, 2022)
In the decisive responses to protest movements in Ethiopia and Cameroon between 2015 and 2018, state control and repression were facilitated by colonial-corporate digital infrastructures and neo-imperial techno-political configurations. In both cases, resistance was met with pervasive state-initiated and corporate-sanctioned internet shutdowns and disruptions. I situate these techno-political practices within the longue durée of coloniality to argue that the state suspension of internet connectivity is a form of infrastructural harm; an intentional violence made socially and structurally possible by the colonial configurations of infrastructure. My analysis draws from five years of digital ethnography and ethnographic fieldwork, including 13 months in Jimma, Ethiopia and nine months in Yaoundé, Cameroon. I mobilize a decolonial praxis that unmasks practices of authoritarian control within global racial coloniality, and seeks to foster cross-fertilizations of struggle and resistance praxis.